Accounting and Accountability in Religious Organizations: An Islamic Contemporary Scholars’ Perspective - Basri, Hasan; A. K., Siti Nabiha; Abd. Majid, M. Shabri (Gadjah Mada International Journal of Business, 2016)
The purpose of this article is to discuss the views and opinions of contemporary Muslim scholars on organisational accountability in Islam. The paper is based on in-depth semi-structured interviews and a review of the relevant documents. Eighteen interviews with twelve Muslim scholars, two ulamas (mufti), two organisational donors, and two relevant government officers, both in Indonesia and in Malaysia were, respectively, conducted. The Muslim scholars interviewed perceived that accounting and accountability activities are not contradictory to Islamic teachings. The accountability relationship in Islam is viewed as not only fulfilling the legal requirements, but also fulfilling the relationship with God. The findings clearly indicate that a formal accountability mechanism is strongly encouraged in Islam, and financial reporting is viewed as essential in enhancing the accountability of Islamic religious organizations. Therefore, any organization dealing with community funds must demonstrate its financial accountability formally; i.e., through written reports. Thus, public or community trust in the organisation cannot replace the accountability mechanism.